Biosynthesis of Gold Nanoparticles Using Wuluh Star Fruit (Averrhoa bilimbi) for Chromium Analysis - Dewi, Ria Kemala; Firdaus, M. Lutfi; Nursa'adah, Euis (Universitas Pendidikan Mandalika, 2024)
One of the heavy metals that can pollute waters is the heavy metal chromium (Cr). Chromium has many important roles in life. Chromium material is widely used by humans for various purposes, especially in the industrial world. However, the large number of uses of chromium in the industrial world and the waste it generates can have a negative impact on the environment and human health. One way to deal with chromium pollution is by analyzing the presence of chromium in waters. The aim of this research is to analyze the presence of chromium using a simple, effective, economical and accurate method, namely the biosynthesis of gold nanoparticles using samples of starfruit (Averrhoa bilimbi) as a bioreductor rich in ascorbic acid, with a colorimetric method, namely a method based on the aggregation of gold nanoparticles with ascorbic acid from starfruit, which causes a shift in plasmons and causes color changes that can be seen by the eye. Based on the analysis results, data was obtained that gold nanoparticles synthesized from the starfruit bioreductor can detect chromium with a concentration of 10 ppm with optimum conditions at pH 5, temperature 75oC, optimum incubation time of 5 minutes and gold nanoparticles are selective and sensitive for detecting chromium.